Mitochondrial Signature in Human Monocytes and Resistance to Infection in C. elegans During Fumarate-Induced Innate Immune Training - Pérez-Hernández, C. Angélica; Kern, Carina C.; Butkeviciute, Egle; McCarthy, Elizabeth; Dockrell, Hazel M.; Moreno-Altamirano, María Maximina Bertha; Aguilar-López, Bruno A.; Bhosale, Gauri; Wang, Hongyuan; Gems, David; Duchen, Michael R.; Smith, Steven G.; et al. (Frontiers in Immunology, 2020)
Monocytes can develop immunological memory, a functional characteristic widely recognized as innate immune training, to distinguish it from memory in adaptive immune cells. Upon a secondary immune challenge, either homologous or heterologous, trained monocytes/macrophages exhibit a more robust production of pro-inflammatory cytokines, such as IL-1β, IL-6, and TNFα, than untrained monocytes. Candida albicans, β-glucan, and BCG are all inducers of monocyte training and recent metabolic profiling analyses have revealed that training induction is dependent on glycolysis, glutaminolysis, and the cholesterol synthesis pathway, along with fumarate accumulation; interestingly, fumarate itself can induce training. Since fumarate is produced by the tricarboxylic acid (TCA) cycle within mitochondria, we asked whether extra-mitochondrial fumarate has an effect on mitochondrial function. Results showed that the addition of fumarate to monocytes induces mitochondrial Ca2+ uptake, fusion, and increased membrane potential (Δψm), while mitochondrial cristae became closer to each other, suggesting that immediate (from minutes to hours) mitochondrial activation plays a role in the induction phase of innate immune training of monocytes. To establish whether fumarate induces similar mitochondrial changes in vivo in a multicellular organism, effects of fumarate supplementation were tested in the nematode worm Caenorhabditis elegans. This induced mitochondrial fusion in both muscle and intestinal cells and also increased resistance to infection of the pharynx with E. coli. Together, these findings contribute to defining a “mitochondrial signature” associated with the induction of innate immune training by fumarate treatment, and to the understanding of whole organism infection resistance.